2020
DOI: 10.3389/fpsyg.2020.01493
|View full text |Cite
|
Sign up to set email alerts
|

Resident’s Perspective on Developing Community-Based Tourism – A Qualitative Study of Muen Ngoen Kong Community, Chiang Mai, Thailand

Abstract: Community-Based Tourism (CBT) has been presented as an alternative to sustaining tourism development in developing countries. This tourism model offers local residents an opportunity to manage natural and cultural resources in order to promote the local economy and generate greater benefits. The objective of the study is to investigate the benefits and challenges of CBT as well as solutions to address identified shortcomings by studying Muen Ngoen Kong community in Chiang Mai, Thailand. In order to achieve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 65 publications
(110 reference statements)
1
35
0
3
Order By: Relevance
“…Community tourism (sometimes called community-based tourism: CBT), is an alternative form of tourism aiming at sustaining tourism development and provides local residents with an opportunity to manage and control natural and cultural resources (Lo and Janta, 2020) in order to promote the local economy. Studies have suggested CBT as a sustainable model for maximizing local socio-economic benefits of tourism and minimizing negative environmental impacts (Ruiz-Ballesteros and Hernandez-Ramirez, 2010).…”
Section: Community-based Tourismmentioning
confidence: 99%
“…Community tourism (sometimes called community-based tourism: CBT), is an alternative form of tourism aiming at sustaining tourism development and provides local residents with an opportunity to manage and control natural and cultural resources (Lo and Janta, 2020) in order to promote the local economy. Studies have suggested CBT as a sustainable model for maximizing local socio-economic benefits of tourism and minimizing negative environmental impacts (Ruiz-Ballesteros and Hernandez-Ramirez, 2010).…”
Section: Community-based Tourismmentioning
confidence: 99%
“…Intangible cultural heritage display in cultural tourism is an important channel to provide novelty and nostalgia. Common types of cultural tourism related to ICH mostly include digital tourism of legends and folklore (Vassiliadi et al, 2018) and community-based cultural ecotourism (Lo and Janta, 2020). Digital tourism carries out cultural experiences through digital narrative.…”
Section: Cultural Tourism and Intangible Cultural Heritagementioning
confidence: 99%
“…For example, through the digital narration of the volcanic eruption scene of Pompeii ancient city by MR technology, we can get a higher sense of experience (Vassiliadi et al, 2018). In terms of community tourism (Lo and Janta, 2020), it is important to empower communities, involve local residents, cultivate cultural resources, and ultimately maintain the sustainability of the overall tourism resources.…”
Section: Cultural Tourism and Intangible Cultural Heritagementioning
confidence: 99%
See 1 more Smart Citation
“…Without creating opportunities for residents to participate in the decisionmaking process around benefits generated from the tourism development, the decision is more complicated. According to this challenge, some community members are operating against stronger competitors and poor market conditions (Lo and Janta, 2020).…”
Section: Introductionmentioning
confidence: 99%